2022
DOI: 10.1126/sciadv.abm5859
|View full text |Cite
|
Sign up to set email alerts
|

Common and species-specific molecular signatures, networks, and regulators of influenza virus infection in mice, ferrets, and humans

Abstract: Molecular responses to influenza A virus (IAV) infections vary between mammalian species. To identify conserved and species-specific molecular responses, we perform a comparative study of transcriptomic data derived from blood cells, primary epithelial cells, and lung tissues collected from IAV-infected humans, ferrets, and mice. The molecular responses in the human host have unique functions such as antigen processing that are not observed in mice or ferrets. Highly conserved gene coexpression modules across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Studies reported herein provide the first key insights regarding the regulation, localisation and antiviral activity of fMx1, noting that previous studies have performed comprehensive transcriptional analyses of ISGs, including fMx1 and fMx2, in the blood and lungs of IAV-infected ferrets 42 . Our finding that fMx1 can inhibit IAV infection and replication, despite its similarity to canine Mx1 (which does not inhibit IAV), provides avenues for further research to determine the influence of specific Mx1 regions and residues which modulate the potency of anti-IAV activity.…”
Section: Discussionmentioning
confidence: 87%
“…Studies reported herein provide the first key insights regarding the regulation, localisation and antiviral activity of fMx1, noting that previous studies have performed comprehensive transcriptional analyses of ISGs, including fMx1 and fMx2, in the blood and lungs of IAV-infected ferrets 42 . Our finding that fMx1 can inhibit IAV infection and replication, despite its similarity to canine Mx1 (which does not inhibit IAV), provides avenues for further research to determine the influence of specific Mx1 regions and residues which modulate the potency of anti-IAV activity.…”
Section: Discussionmentioning
confidence: 87%
“…To investigate the role of BAG6 during IAV infection in vivo , BAG6-knockdown mice were generated using a peptide-conjugated phosphorodiamidate morpholino oligomers (PPMOs) before PR8 virus (100 TCID 50 ) or mock infection ( Fig 3A ). PPMOs are sequence-specific antisense agents that can be administered intranasally to elicit a transient reduction in the expression of the targeted gene product in the lungs of treated mice [ 25 28 ]. The successful depletion of BAG6 in lung by BAG6-targeting PPMO (PPMO-BAG6) was confirmed by western blotting compared with PPMO control (PPMO-NC) before and after virus infection ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of mice to normoxic hypercapnia downregulated AMØ expression of genes involved in multiple GO processes that are likely relevant to host defense against IAV, including innate immune response, cell migration, chemotaxis, inflammatory response, response to IFN-β, complement activation, regulation of IFN-γ production, and response to virus. Specific genes with documented roles in host defense against influenza and other viral infections that were downregulated in AMØs include Ripk3 (30), Msr1 (31), Cxcl17 (32), C1q (33), C4a (34), C4b (35), Cfh (36), Ch25h (37), Ccl17 (38), Cd200 (39), Gbp6 (40), Iigp1 (41), Pyhin1 (42), and the IFN-stimulated antiviral effector Oasl2 (43). Myeloid Zfhx3 deficiency abrogated hypercapnic downregulation of GO processes in AMØs associated with antiviral host defense, including innate immune response, complement activation, inflammatory response, and chemotaxis.…”
Section: Discussionmentioning
confidence: 99%